Arts-Research-Education Connections and Directions (Studies in Arts-Based Educational Research,, 2018)
Drawing from an international authorship and having global appeal, this book scrutinizes, suggests and aggravates the relationships, boundaries and connections between arts, research and education in various contexts. Building upon existing publications in the field of arts-based educational research, it deliberately connects and disconnects the terms in order to expose and broaden the scope of this field thereby encouraging fresh perspectives. This book portrays both contemporary theoretical prospects as well as contemporary examples of practice. It also presents work of emerging scholars, thereby 'growing the field'. The book includes academic text-based chapters, as well as poetry, narrative fiction, visual essays, and combinations of text-image-sound/video that demonstrate performance of music, theatre, exhibition and dance. This book provides and provokes critical dialogue about the forms, representations, dissemination and intersections of the arts, research and education. This is a focused collection and resource for scholars and students with an international authorship, perspective and audience.